RAGAM HIAS PADA MASJID AINUL YAQIN GRESIK - Pradana, Rizal Wahyu Bagas (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Ainul Yaqin Mosque is one of the guardian mosques in Gresik Regency, East Java. The establishment of this mosque building is inseparable from the character of Sunan Giri and his descendants. The peculiarity of this mosque is the presence of ornament with Majapahit style in the building. Therefore, a study was carried out with the aim of describing the ornaments items found in the Ainul Yaqin Mosque building. The results showed that the decorative items contained in the Ainul Yaqin Mosque building can be divided into three groups, among others: 1) Ornaments of Geometric includes the motives of solar majapahit and mega overcast. 2) Ornaments of flora includes the motifs of lungs, tlacapan, saton, kebenan, padma, and patran. 3) Ornaments of living things include banaspati and naga motifs, 4) Ornaments of still life includes mustaka, praba, and banyu tetes. The ornament that is available at Ainul Yaqin Mosque is created not only as part of a building unit, but also has another function, namely adding value to the beauty of the mosque building. Keywords: architecture, mosque, art, ornament